Diabetic Retinopathy and Peripapillary Retinal Thickness - Cho, Hee Yoon (The Korean Ophthalmological Society, 2010)
PURPOSE: To assess the diagnostic efficacy of macular and peripapillary retinal thickness measurements for the staging of diabetic retinopathy (DR) and the prediction of disease progression. METHODS: In this prospective study, 149 diabetic patients (149 eyes) and 50 non-diabetic control subjects were included. Baseline optical coherence tomography was employed to measure retinal thickness in the macula (horizontal, vertical, and central) and the peripapillary zone (superior, inferior, nasal, and concentric to the optic disc). Seven baseline parameters were correlated with the DR stages identified by fluorescein angiography. Baseline retinal thickness was compared between groups of patients requiring panretinal photocoagulation (PRP) within 6 months (PRP group) and patients not requiring PRP (No-PRP group). RESULTS: Macular and peripapillary retinal thicknesses in diabetic subjects were significantly greater than that in normal controls (p<0.05). All retinal thickness parameters, and particularly peripapillary circular scans, tended to increase with increasing DR severity (p<0.05). The baseline thicknesses of the peripapillary circular scans were greater in the PRP group than in the no-PRP group (p<0.05). CONCLUSIONS: Peripapillary retinal thickness may prove to be a useful criterion for DR severity and may also serve as an indicator of disease progression.